FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STUNTING PADA ANAK KELAS SATU DI SDI TAQWIYATUL WATHON, DAERAH PESISIR KOTA SEMARANG - Aisyah Aisyah; Suyatno Suyatno; M . Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Nutritional intake not needed by long term with infectious diseases on toddlers caused stunting in children in the future, especially during elementary school. The prevalence of stunting in the north of Semarang was 28,23% which had a chance to stunting on elementary school. Stunting in children new elementary school was health indicator or reflection of nutrition status that had strong relation with economic status.The study purpose was to determine the factors associated with stunting in children new school at SDI Taqwiyatul Wathon. This study used analytical survey with cross sectional approach. The population on the study were collected by measuring 97 children in the class one, while the sample study is 7 years old children (32 respondent) with purposive sampling. Sampels were obtained through interview of questionnaire. Data were analyzed by chi-square and uji fisher extract. The result of this study showed there were stunting new elementary school (25%). While, there was no relation between stunting with mother's work (p=0,154), mothers education (p=0,147), family income (p=0,295), nutritional parenting (p=0,577), health care parenting(p=0,633), personal hygiene parenting (p=0,309), and infectious diseases (p=0,425). There is a tendency between mother’s work, high family income, and less parenting with stunting. Therefore, study suggest that for parents to pay more attention to parenting, especially in the variety of food served.